2020
DOI: 10.1088/1755-1315/457/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of morpho-agronomic characterization Apple cucumber: a new variety of melon from Indonesia

Abstract: The Cucurbitaceae has been known to many farmers as a plant that has beneficial for agriculture industries. For decades plants that belong to Cucurbitaceae such as cucumber (Cucumis sativus), watermelon (Citrullus lanatus), and melon (Cucumis melo) has been cultivated to meet consumer needs. In Indonesia, a new variety of melon has been discovered namely apple cucumber. This new variety has blurred the difference between melon and cucumber due to the vegetative resemblance. This research was conducted to clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…The growth findings were comparable with those of Akhoundnejad and Sevgin (2019), who detected a distribution of main stem lengths (MSL) ranging from 40.51 to 68.42 cm across melon genotypes. Our main stem diameter (MSD) finding was larger than that of Yusuf et al (2020), who reported a stem diameter range of 0.84 to 0.92 cm among three melon genotypes, Akhoundnejad and Sevgin (2019), who reported a range of 0.6 to 1 cm MSD, and Saputro et al (2020), who reported an MSD of 0.8 cm. Our study's leaf length (LL) and leaf width (LW) were lower than those reported by Yusuf et al (2020), which varied from 12 to 16 cm and 18 to 22 cm, respectively, and Zhang et al (2012), who observed an average of 13.12 and 15.06 cm for LL and LW, respectively, across nine melon genotypes.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...contrasting
confidence: 81%
See 2 more Smart Citations
“…The growth findings were comparable with those of Akhoundnejad and Sevgin (2019), who detected a distribution of main stem lengths (MSL) ranging from 40.51 to 68.42 cm across melon genotypes. Our main stem diameter (MSD) finding was larger than that of Yusuf et al (2020), who reported a stem diameter range of 0.84 to 0.92 cm among three melon genotypes, Akhoundnejad and Sevgin (2019), who reported a range of 0.6 to 1 cm MSD, and Saputro et al (2020), who reported an MSD of 0.8 cm. Our study's leaf length (LL) and leaf width (LW) were lower than those reported by Yusuf et al (2020), which varied from 12 to 16 cm and 18 to 22 cm, respectively, and Zhang et al (2012), who observed an average of 13.12 and 15.06 cm for LL and LW, respectively, across nine melon genotypes.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...contrasting
confidence: 81%
“…Our study's leaf length (LL) and leaf width (LW) were lower than those reported by Yusuf et al (2020), which varied from 12 to 16 cm and 18 to 22 cm, respectively, and Zhang et al (2012), who observed an average of 13.12 and 15.06 cm for LL and LW, respectively, across nine melon genotypes. The number of lateral stems (NLS) results agreed with those of Saputro et al (2020), who measured four lateral branches per plant, but were lower than those of Zhang et al (2012). These differences could be related to genetic differences as well as climate factors.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...supporting
confidence: 61%
See 1 more Smart Citation
“…Not only this study, a new subspecies through phylogenetic analysis has been proposed by many researchers in angiosperm group (Zeng et al 2014) such as in Dasyphyllum (Ferreira et al 2019). On the basis of detailed quantitative and qualitative morpho-agronomic characters (141 characters), these two plants are different (Saputro et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…To address this issue, diversity is a primary priority in species. Different morphological, phenological, and physiological approaches (Pandey et al 2021;Saputro et al 2020;Singh et al 2020) have been used to assess genetic variation in melon. Morphological analyses are the most essential criteria in the initial assessment of genetic variation for melon genotype and cultivar categorization and identi cation.…”
Section: Introductionmentioning
confidence: 99%